2001
DOI: 10.1002/1097-0142(20010115)91:2<294::aid-cncr1001>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy influences bone marrow infiltration in patients with splenic marginal zone cell lymphoma with or without villous lymphocytes

Abstract: BACKGROUND Splenic marginal zone cell lymphoma (SMZL) is a low grade B‐cell lymphoma in which patients can have circulating villous lymphocytes and can show a peculiar intrasinusoidal bone marrow (BM) infiltration. Splenectomy is the reported treatment of choice for these patients. The objective of this study was to evaluate the effects of splenectomy on patients with BM lymphomatous infiltration. METHODS BM biopsies of 16 patients with SMZL were studied morphologically and immunohistochemically. In 12 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 47 publications
1
21
0
2
Order By: Relevance
“…11,17,21 It has been shown that the extent of bone marrow infiltration by lymphoma may increase after splenectomy. 22 As in previous reports, this study highlights that splenectomy is related to better OS and CSS as determined with univariate analysis. In multivariate analysis, however, splenectomy did not retain an independent prognostic value.…”
Section: Discussionsupporting
confidence: 81%
“…11,17,21 It has been shown that the extent of bone marrow infiltration by lymphoma may increase after splenectomy. 22 As in previous reports, this study highlights that splenectomy is related to better OS and CSS as determined with univariate analysis. In multivariate analysis, however, splenectomy did not retain an independent prognostic value.…”
Section: Discussionsupporting
confidence: 81%
“…The pattern of infiltration is typically intrasinusoidal and with the progression of the disease, especially after splenectomy, becomes nodular. 19 In advanced cases, the combination of intrasinusoidal and nodular infiltration is highly characteristic, although not entirely specific. 20 Frequently the follicles in the BM show a preserved germinal center surrounded by a rim of MZ cells.…”
Section: Bm Aspirate and Histologymentioning
confidence: 99%
“…5,35 When treatment is indicated (i.e., occurrence of a large symptomatic splenomegaly and/or cytopenia), splenectomy is the treatment of choice. 31 Splenectomy is beneficial in terms of improvement of performance status and correction of cytopenias 4,31 This benefit, which is due to the disappearance of hypersplenism but also the reduction of mar- Abbreviations: HCV, hepatitis C virus; IFN, interferon; LDH, lactate dehydrogenase; R-CHOP, rituximab, vincristine, doxorubicin, cyclophosphamide, predisolone; R-FC, rituximab, fludarabine, cyclophosphamide row infiltration after splenectomy, 36 persists for years, with an interval before requiring further treatment of over 5 years, even if the patient develops progressive lymphocytosis. 31 Chemotherapy based on alkylating agents (chlorambucil or cyclophosphamide) or purine analogues (fludarabine) has also been reported as an effective treatment in non-randomized studies or in retrospective analyses.…”
Section: Treatmentmentioning
confidence: 99%